A new coast : strategies for responding to devastating storms and rising seas - Peterson, Jeffrey L. (Island Press, 2019)
More severe storms and rising seas will inexorably push the American coastline inland with profound impact on communities, infrastructure, and natural systems. In A New Coast, Jeffrey Peterson draws a comprehensive picture of how storms and rising seas will change the coast. Peterson offers a clear-eyed assessment of how governments can work with the private sector and citizens to be better prepared for the coming coastal inundation. Drawing on four decades of experience at the Environmental Protection Agency and the United States Senate, Peterson presents the science behind predictions for coastal impacts. He explains how current policies fall short of what is needed to effectively prepare for these changes and how the Trump Administration has significantly weakened these efforts. While describing how and why the current policies exist, he builds a strong case for a bold, new approach, tackling difficult topics including: how to revise flood insurance and disaster assistance programs; when to step back from the coast rather than build protection structures; how to steer new development away from at-risk areas; and how to finance the transition to a new coast. Key challenges, including how to protect critical infrastructure, ecosystems, and disadvantaged populations, are examined. Ultimately, Peterson offers hope in the form of a framework of new national policies and programs to support local and state governments. He calls for engagement from the private sector and local and national leaders in a "campaign for a new coast." A New Coast is a compelling assessment of the dramatic changes that are coming to America's coast. Peterson offers insights and strategies for policymakers, planners, and business leaders preparing for the intensifying impacts of climate change along the coast. --